Fuel‐Free Synthetic Micro‐/Nanomachines - Xu, Tailin; Gao, Wei; Xu, Li‐Ping; Zhang, Xueji; Wang, Shutao (Advanced materials (Weinheim), 2017)
Inspired by the swimming of natural microorganisms, synthetic micro‐/nanomachines, which convert energy into movement, are able to mimic the function of these amazing natural systems and help humanity by completing environmental and biological tasks. While offering autonomous propulsion, conventional micro‐/nanomachines usually rely on the decomposition of external chemical fuels (e.g., H2O2), which greatly hinders their applications in biologically relevant media. Recent developments have resulted in various micro‐/nanomotors that can be powered by biocompatible fuels. Fuel‐free synthetic micro‐/nanomotors, which can move without external chemical fuels, represent another attractive solution for practical applications owing to their biocompatibility and sustainability. Here, recent developments on fuel‐free micro‐/nanomotors (powered by various external stimuli such as light, magnetic, electric, or ultrasonic fields) are summarized, ranging from fabrication to propulsion mechanisms. The applications of these fuel‐free micro‐/nanomotors are also discussed, including nanopatterning, targeted drug/gene delivery, cell manipulation, and precision nanosurgery. With continuous innovation, future autonomous, intelligent and multifunctional fuel‐free micro‐/nanomachines are expected to have a profound impact upon diverse biomedical applications, providing unlimited opportunities beyond one's imagination. Fuel‐free synthetic micro‐/nanomachines powered by external stimuli are able to swim efficiently in biologically relevant environments. Tremendous progress made in the past decade to develop different synthesis strategies for designing and fabricating fuel‐free micro‐/nanomotors with different functionalities is reviewed. These artificial nanomachines can achieve predetermined tasks in biomedical applications.